Response of Mungbean [Vigna radiata (L.)Wilczek] Varieties to Plant Spacing under Irrigation at Gewane, Northeastern Ethiopia - Nuru Seid Tehulie; Tarikua Fikadu; Jhon Hardy Purba (Agro Bali : Agricultural Journal, 2021)
Production of mungbean has been increasing in Ethiopia because of its high importance as a source of protein and foreign exchange earnings. Determination of appropriate plant density for the varieties of mungbean can increase its productivity. Therefore, an experiment was conducted to determine the effect of inter and intra row spacing on growth, yield components and yield of mung bean varieties under irrigation. The treatments consisted of factorial combinations of three inter row spacing (30, 40, and 50 cm), three-intra row spacing (5, 10 and 15 cm) and two mungbean varieties (N-26 and MH-97) laid out in randomized complete block design with three Replications. The main effect of varieties, inter row spacing and intra row spacing was highly significant and significant on plant height, secondary branch and where the longest plant height (41.71 cm) was for variety MH-97 and from 5 cm intra row spacing, respectively and maximum number of secondary branch was recorded for variety MH-97 (8.91) and from 15cm intra row and 50cm inter row spacing, respectively.  The interaction effect of the variety, inter and intra row spacing was highly significant on number of primary branch per plant, number of pod per plant and crop stand count percentage where the highest number of primary branches (7.00) was recorded from variety MH-97 at 50 cm inter row spacing and highest number pods per plant (30.15) were recorded for variety MH-97 at 40 cm inter row and (31.34) at 15cm intra row spacing. Where the highest crop stand count at harvest were recorded from variety MH-97  (97.00%) at 40 cm inter row spacing .The main effect of inter row spacing and intra row spacing were highly significant and significant on above ground dry biomass and the highest above ground dry biomass at inter row spacing of 30 cm ( 5968.8 kg ha-1) and intra row spacing 5cm 6145.9 kg ha-1).The main effect of variety, inter-row and intra-row spacing were highly significant on harvest index and grain yield where the highest harvest index was from variety MH-97 (20.91%), inter row spacing of 40 cm which give (21.18%) and intra row spacing 10 cm which give  (20.30%) and the highest grain yield from Variety MH-97 (1117.94 kg ha-1), inter row spacing 40 cm (1213.75 kg ha-1) and intra row spacing 10 cm which give (1151.67 kg ha-1) However, this tentative generalization based one season at one location requires further studies over years and locations to give a valid recommendation.